Herbal Medicine: A New Ray of Hope for Vitiligo Patients - Shaikh Habeeba; Shaikh Siddiqua (Current Overview on Pharmaceutical Science Vol. 3, 2023)
Vitiligo is a depigmentation disorder with complex causes. Nonetheless, recent progress has been made to unravel the pathophysiology of vitiligo. In this chapter, we provide an overview of the herbs that have been used in clinical studies to treat vitiligo and highlight herbs that are known to be effective. Herbs including Ammi visnaga L., Camellia sinensis, Ginkgo biloba, and Psoralea corylifolia L. have been highlighted because of their traditional applications. The research for vitiligo drugs today requires enormous effort. We strongly believe that this chapter may help to rationalize the use of a novel herbal medicine in the treatment of vitiligo.